Association between dietary knowledge and overweight and obesity in Chinese children and adolescents: Evidence from the China Health and Nutrition Survey in 2004-2015. - Zhen Xu; Yibin Zhao; Jingjing Sun; Lisi Luo; Yu Ling (PLoS ONE, 2022)
Objective To assess whether dietary knowledge of Chinese children and adolescents and their mothers was associated with childhood and adolescent overweight and obesity. Methods This cross-sectional study obtained data from the China Health and Nutrition Survey (CHNS) between 2004 and 2015. Dietary knowledge of children and adolescents and their mothers was assessed by asking questions and statements on diets, and clustered by K-means clustering. Body mass index (BMI) and waist circumference (WC) were used to evaluate overweight and obesity among children and adolescents. The association of dietary knowledge with childhood and adolescent overweight and obesity was evaluated by multivariate regression analysis, with odds ratios (ORs) and 95% confidence intervals (CIs) calculated. Results A total of 2,338 children and adolescents were included. Children and adolescents with low dietary knowledge were demonstrated to have significantly higher risks of BMI-defined overweight or obesity (OR = 1.66, 95%CI = 1.21-2.28, P = 0.002), and WC-defined obesity (OR = 1.52, 95%CI = 1.12-2.06, P = 0.007) than those with high dietary knowledge. Compared with high dietary knowledge in mothers, low dietary knowledge was associated with significantly elevated risks of BMI-defined overweight or obesity (OR = 1.48, 95%CI = 1.08-2.02, P = 0.014), and WC-defined obesity (OR = 1.59, 95%CI = 1.18-2.16, P = 0.003). Furthermore, significantly increased odds of BMI-defined overweight or obesity and WC-defined non-obesity in children and adolescents were related to low dietary knowledge versus high dietary knowledge of children and adolescents (OR = 1.72, 95%CI = 1.08-2.74, P = 0.023), while there was no association of BMI-defined non-overweight and non-obesity and WC-defined obesity with dietary knowledge among children and adolescents (OR = 1.35, 95%CI = 0.89-2.04, P = 0.161). Additionally, no association was found between dietary knowledge of mothers and BMI-defined overweight or obesity and WC-defined non-obesity among children and adolescents (OR = 1.39, 95%CI = 0.89-2.17, P = 0.155), while low dietary knowledge of mothers was associated with increased odds of BMI-defined non-overweight and non-obesity and WC-defined obesity in children and adolescents (OR = 1.58, 95%CI = 1.03-2.43, P = 0.036). Conclusion Dietary knowledge of children and adolescents and their mothers was associated with childhood and adolescent overweight and obesity. Dietary knowledge of children and adolescents negatively related to the risk of BMI-defined overweight or obesity, and dietary knowledge of mothers to odds of WC-defined obesity.